KEEFEKTIFAN MEDIA LEARNING MANAGEMENT SYSTEM BERBASIS MOODLE TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN IPAS KELAS V SD - Prameswari, Dina; Nafiah; Ibrahim, Muslimin; Hartatik, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low critical thinking ability of students as indicated by difficulties in analyzing story problems and drawing conclusions. The purpose of this study is to describe the implementation of science learning using Moodle-based Learning Management System media and test the effectiveness of the media on students' critical thinking abilities. This study uses a quantitative approach with a pre-experimental method of one group pretest–posttest design. The research subjects were fifth-grade students at Antawirya Islamic Javanese School Elementary School with a sample of 30 students from class V-B. Data collection techniques used observation of learning implementation and the administration of pretests and posttests, while data analysis techniques used percentage of implementation and N-Gain tests. The results showed that the average pretest score of students' critical thinking abilities was 44.17 which is classified as low and has not reached the Minimum Completion Criteria (KKM). After being given treatment, the average posttest score increased to 88.50 which is classified as high and exceeds the KKM. The results of the N-Gain analysis showed an average of 0.78 with a high category. Thus, the use of Moodle-based Learning Management System media has proven effective in improving students' critical thinking skills in the science subject.